PENGARUH SUPLEMANTASI VITAMIN C DIBANDINGKAN DENGAN MULTI VITAMIN-MINERAL TERHADAP STATUS ZAT GIZI ANTIOKSIDAN PADA WANITA PEKERJA - Ernawati, Fitrah; ., Rimbawan; Riyadi, Hadi; T.Wibawan, I.Wayan; ., Muhilal (GIZI INDONESIA, 2009)
EFFECT OF THE VITAMIN C SUPLEMENTATION TOWARD MULTI VITAMIN-MINERAL ON THE STATUS OF NUTRITIONAL ANTIOXIDANT IN WOMAN WORKERSMicronutrients, both vitamins and minerals are needed by the body in limited quantities, but their roleis essential to the body. To fulfill vitamin and mineral requirements, consumption of variant andbalanced diet is needed because most vitamins and minerals are not produced by our body. Foodsupplements can be a good alternative in providing sufficient amount of micronutrient if intake fromdietary sources are not enough. This research was intended to analyse the effect of multi vitaminmineral (MVM) supplementationcompared to a single nutrient supplementation (Vit C 1000 mg) ondietary antioxidant status. It was conducted on Februari 2008and thedesign of this research was adouble blind randomized controlled trial. There were 92 samples aged 20-45 years old, healthy(physically and clinically), did not consume alcohol, did not smoke and were willing to partipate in theresearch. Multi vitamin-mineral supplementation increased serum concentration of vitamin E andsuperoxide dismutase (SOD) significantly(p<0.05), while single supplementation of vitamin C 1000 mgimproved only vitamin C status. Suplementation of multi vitamin-mineral reduced free radicals byimproving superoxide dismutase (SOD) status. Keywords: multi vitamin-mineral supplementation, superdioxide dismutase status, vitamin Estatus, viin C status.